A Necessary Inhumanity?. Issue 2 (1st December 2000) - Richardson, Ruth
Abstract : It is argued that the phrase "Necessary Inhumanity" more accurately describes the alienation required of doctors in some circumstances, than do modern sanitised coinages such as 'clinical detachment'. 'Detachment' and 'objectivity' imply separation, not engagement: creating distance not only from patients, but from the self: the process may well be required, but where it becomes too extreme or prolonged, it can damage everybody, including patients, family members, doctors themselves, and wider society. An awareness of the history of health care in the context of our society might assist self reflection–might help keep initiates in touch with the culture they have been induced to leave and might help them remain humane despite the bruising process of training.